OPTIMASI CROSPOVIDONE DAN POLYVINYL PYRROLIDONE K-30 DALAM FORMULASI ORALLY DISINTEGRATING TABLET (ODT) SALBUTAMOL SULFAT - Lusia Oktora Ruma Kumala Sari; Via Rahmatia; Kuni Zu’aimah Barikah (Jurnal Kesehatan Islam : Islamic Health Journal, 2023)
Abstract. The objective of the present study was to optimize crospovidone as a superdisintegrant and polyvinyl pyrrolidone (PVP) K-30 as a binder in ODT salbutamol sulphate. ODT salbutamol sulphate was made by direct compression technique. Optimization was carried out by the factorial design method using Design Expert 11.0 software with optimized responses, including hardness, friability, and disintegration time. The result showed that crospovidone affected the decrease in the disintegration time of ODT. PVP K-30 affected decreasing friability and increasing hardness and disintegration time of ODT. The interaction of crospovidone and PVP K-30 affected the decrease in ODT's disintegration time. The optimum formula contained 5% crospovidone and 1,5% PVP K-30, resulting in 5,087 kg of hardness, 0,743% friability, and 45,350 seconds of disintegration time. ODT salbutamol sulphate’s optimum formula dissolved 93,082% after 30 minutes. Kata Kunci Orally disintegrating tablet; salbutamol sulphate; crospovidone; pvp k-30